Intravital Correlative Microscopy: Imaging Life at the Nanoscale. Issue 11 (November 2016) - Karreman, Matthia A.; Hyenne, Vincent; Schwab, Yannick; Goetz, Jacky G.
Abstract : Studying key biological events within complex model systems relies on dynamic and functional imaging at optimum spatial and temporal resolutions. Intravital correlative light and electron microscopy (intravital CLEM) combines imaging living multicellular model systems with electron microscopy, and offers full ultrastructural details of dynamic or transient events in vivo . However, routine use of intravital CLEM is hindered by multiple technological challenges faced when targeting a micron-size object (e.g., single cells or organelles) in a complex living organism. Recently, various approaches have been developed to overcome these limitations. In this review we outline the current methods and present the power of intravital CLEM in different fields of research. Finally, we describe approaches that will make intravital CLEM a routine, quantitative method for high-resolution cell biology in vivo . Trends: Modern imaging for life sciences is performed on model organisms. It aims at integrating functional information obtained in vivo with high spatial resolution. Intravital CLEM uniquely enables the visualization of key biological events in living multicellular organisms and at high resolution. Bimodal probes are specifically developed to mark the event of interest for in vivo and EM imaging. Automating correlative workflows to enable higher throughput is a prerequisite for routine and quantitative applications.